Research progress on cuproptosis and copper related anti-tumor therapy - Yichen Li; Lifei Han; Haolin Hu (Discover Oncology)
Abstract Copper is a trace element which is essential for biological organisms, and its homeostatic balance is important for living organisms to maintain the normal function. When the copper homeostasis is disordered, the cellular function and structure will be disrupted. Excess copper cause oxidative stress and DNA damage in cells, thereby inducing regulated cell death such as apoptosis and necroptosis. Excess copper in mitochondria can bind to lipoylated proteins in the tricarboxylic acid (TCA) cycle and cause them to aggregate, resulting in proteotoxic stress and eliciting a novel cell death modality: cuproptosis. Cancer cells have a greater demand for copper compared to normal tissue, and high levels of copper ions are closely associated with tumour proliferation and metastasis. The anti-tumor mechanisms of copper include the production of oxidative stress, inhibition of the ubiquitin–proteasome system, suppression of angiogenesis, and induction of copper-dependent cell death. Targeting copper is one of the current directions in oncology research, including the use of copper ion carriers to increase intracellular copper levels to induce oxidative stress and cuproptosis, as well as the use of copper ion chelators to reduce copper bioavailability. However, copper complexes have certain toxicity, so their biosafety needs to be improved. Emerging nanotechnology is expected to solve this problem by utilizing copper-based nanomaterials (Cu-based NMs) to deliver copper ions and a variety of drugs with different functions, thereby improving the anti-tumor efficacy and reducing the side effects. Therefore, a thorough understanding of copper metabolic processes and the mechanism of cuproptosis will greatly benefit anti-tumor therapy. This review summarizes the processes of copper metabolism and the mechanism of cuproptosis. In addition, we discuss the current anti-tumor paradigms related to copper, we also discuss current nanotherapeutic approaches to copper mortality and provide prospective insights into the future copper-mediated cancer therapy.